ChemInform Abstract: Iron‐Catalyzed Efficient Intermolecular Amination of C(sp3)—H Bonds with Bromamine‐T as Nitrene Source. Issue 4 (January 2015) - Wang, Haiyu; Li, Yuxi; Wang, Zhiming; Lou, Jun; Xiao, Yuling; Qiu, Guofu; Hu, Xianming; Altenbach, Hans‐Josef; Liu, Peng
Abstract As sole by product NaBr is formed.